Erosion-corrosion behaviour of nichel resist type D-4 alloy - Low, Louis Bing Xin (2018)
This study investigated the effects of salt concentration and particle impingement angle on the erosion-corrosion rate of Ni-Resist Type D-4 alloy. Ni-Resist Type D-4 samples were tested under three different particle impingement angles (30o, 60o, and 90o) and subjected to two different sodium chloride (NaCl) concentrations (0% and 3.5%). The erosion rate of samples was calculated as a function of contact area and mass loss. In addition, the surface morphology of eroded samples was analysed using Scanning Electron Microscopy (SEM) and X-ray spectroscopy (EDX) methods. Results showed that erosion rate and surface morphology of Ni-Resist Type D-4 alloy have varied significantly based on different experimental conditions of salt concentration and particle impingement angle. Erosion rate of Ni-Resist Type D-4 alloy increased with an increase in particle impingement angle. In addition, the rate of material loss was accelerated when subjected to an increase in NaCl concentration of 3.5%. In-depth analysis of the surface morphology for the different Ni-Resist Type D-4 samples under different conditions of NaCl concentrations and particle impingement angles were well correlated by the erosion rates and the material loss mechanisms involved.